A study on accuracy of predefined screening criteria for selective ordering of chest x-ray in routine medical examination among students enrolling into higher learning institution attending Hospital Universiti Sains Malaysia - Daud, Norwati (2006)
INTRODUCTION: The practice of doing chest x-ray in routine medical examination (RME) is still prevalent in Malaysia although many studies argue the benefit of routine chest x-ray in asymptomatic individuals. There is no standardized RME form used by various institutions in Malaysia. There are also no clear guidelines on who should have a chest x-ray and who should not. Therefore, there is a need to develop a set of screening criteria for selective ordering of chest x-ray in RME to reduce health care cost and to avoid unnecessary radiation risk. OBJECTIVES: The objectives of the study are: 1. To develop an accurate set of screening criteria from literature review. 2. To determine the sensitivity, specificity, positive predictive value and negative predictive value of the predefined screening criteria. The set of screening criteria is intended to be used as a screening tool for selective ordering of chest x-ray in RME 3. To determine the prevalence of abnormal chest x-ray in routine medical examination. 4. To determine the sensitivity, specificity, positive predictive value and negative predictive value of chest x-ray interpretation made by medical officers. The agreement between medical officers and radiologist is also determined. METHODOLOGY: A total of 408 students who came to Hospital Universiti Sains Malaysia between 1st June 2004 and 31st December 2004 participated in the study. They were screened by the predefined screening criteria developed by the researcher. The decision on chest x-ray requirement was determined based on the screening criteria. All the chest x-rays were reported both by medical officers and an appointed radiologist. RESULTS: The results from this study showed that the predefined screening criteria developed by the researcher has a sensitivity, specificity, positive predictive value and negative predictive value of 26.1 o/o, 66.8%, 4.5% and 93.8% respectively. The prevalence of abnormal chest x-ray is 5.64% (95% C.l: 0.03-0.08). The sensitivity, specificity, positive predictive value and negative predictive value of chest x-ray interpretation by medical officers are 17.4%, 98.2%, 36.4% and 95.2% respectively The agreement on chest x-ray interpretation between medical officer and radiologist was poor (kappa=0.206). CONCLUSIONS: From this study, it can be concluded that the prevalence of abnormal chest x-ray in RME is low. The set of screening criteria developed by the researcher is not accurate to be used as a screening tool for detecting abnormal chest x-ray in RME. However, the high negative predictive value means that the probability if a student is not indicated for chest x-ray to have a normal result is high. There is considerable discrepancy between medical officers' chest x-ray interpretation and that of trained radiologist. Chest xray findings did not influence the decision of fitness for enrolment. Further research needs to be done to improve the accuracy of the screening criteria.